Review of the genus Nepaletricha Chandler (Diptera, Rangomaramidae), with description of new species from Thailand and Vietnam - Hippa, Heikki; Chandler, Peter; Papp, László (Zootaxa, 2009)
The genus Nepaletricha consists of the following species: N. mystica Chandler (Nepal), N. furcata sp. n. (Thailand and Vietnam) and N. montana sp. n. (Thailand). The previously unknown female characters are described. The placement of the genus is briefly reviewed and discussed.